New insights into the late Middle Stone Age occupation of Oued el Akarit, southern Tunisia. (November 2021) - Barton, R.N.E.; Belhouchet, L.; Collcutt, S.N.; Aouadi, N.; Albert, P.G.; Douka, K.; Drake, N.; Linderholm, L.; Macphail, R.I.; McLean, D.; Mekki, H.; Peat, D.; et al.
Abstract: This article reports on a new project to investigate the activities of early Homo sapiens in the area of the Chotts 'megalake' in southern Tunisia. Excavations in 2015 and 2019 at Oued el Akarit revealed one of a number of Middle Stone Age (MSA) horizons near the top of a long sequence of Upper Pleistocene deposits. The site identified as Oued el Akarit ( Sondage 8 ) consists of lithic artefacts, bone fragments of large ungulates and pieces of ostrich eggshell. Many of the objects are burnt. Excavation of about nine square metres revealed that these were associated with a lightly trampled and combusted occupation surface. Amongst the identified artefacts were Levallois flakes some of which could be refitted, thereby indicating the generally undisturbed nature of the occupation. The lithic finds also included side scrapers and other tools diagnostic of the MSA but significantly no bifacial or tanged tools. OSL (Optically Stimulated Luminescence) dating of the sediments and AMS (Accelerator Mass Spectrometry) radiocarbon dating of ostrich eggshell have produced uncalibrated age determinations in the range 37, 000–40, 000 years ago, one of the youngest ages for MSA sites in the region. This is the first example of a securely dated later MSA occupation in a riparian environment in south-eastern Tunisia.